It's the customer, stupid! : 34 wake-up calls to help you stay client-focused - Aun, Michael (Wiley, 2011)
Ruthlessly focus on what's convenient for customers, not what's convenient for you. Ninety percent of dissatisfied clients will take their business elsewhere and never tell you why. However, ninety-five percent will become loyal customers again if their needs and problems are addressed and remedied. Speaker and salesperson Michael Aun shares these secrets and many more in It's the Customer, Stupid!, a guide to growing any business by gaining new customers, and, more importantly, by keeping the ones you have happy and coming back for more. This fun-to-read book explains common myths about sale.